Maize-soybean intercropping facilitates chemical and microbial transformations of phosphorus fractions in a calcareous soil - Liu, Jin; Li, Yang; Han, Chaoqun; Yang, Dongling; Yang, Jianjun; Cade-Menun, Barbara J.; Chen, Yuanquan; Sui, Peng (Frontiers in Microbiology, 2022)
Intercropping often substantially increases phosphorus (P) availability to plants compared with monocropping, which could be an effective strategy for soil legacy P recovery and agricultural production. However, the biogeochemical interactions among plants, microbes, and soil that mobilize P remain largely unknown in intercropping systems. Pot experiments with maize-soybean intercropping in a calcareous soil were conducted to investigate the potential chemical and biological transformation mechanisms of inorganic P (Pi) and organic P (Po) using sequential extraction and Illumina MiSeq sequencing. Compared to monocropping of each crop, maize-soybean intercropping significantly enhanced total P uptake of the two crops by mobilizing Ca2-Pi [extracted by bicarbonate (NaHCO3)], Al-Pi/Po [extracted by ammonium fluoride (NH4F)] and Fe-Pi [extracted by sodium hydroxide and sodium carbonate (NaOH-Na2CO3)] fractions. Furthermore, there were significant increases in the organic carbon content and alkaline phosphomonoesterase and phosphodiesterase activities as well as the abundances of Microvirga, Lysobacter, Microlunatus and Sphingomonas under maize-soybean intercropping relative to monocropping. In contrast, compared to monocroppping, insignificant change in the soil pH was observed under maize-soybean intercropping. Therefore, the enhanced P uptake of the maize-soybean intercropping probably resulted from a synergistic effect of rhizosphere organic carbon deposit, increased activities of alkaline phosphomonoesterase and phosphodiesterase, together with the bacteria (Microvirga, Lysobacter, Microlunatus and Sphingomonas) which showed correlation with soil P forms, while the generally recognized rhizosphere acidification was excluded in this investigated calcareous soil. Moreover, the selected bacterial genera exhibited a closer network in the rhizosphere of soybean compared to maize, suggesting the enhanced interactions among bacteria in soybean rhizosphere. These results provide theoretical bases for the recovery of soil legacy P by maize-soybean intercropping.